2021
DOI: 10.1136/rapm-2020-102259
|View full text |Cite
|
Sign up to set email alerts
|

Prospective, randomized, multicenter study of intraosseous basivertebral nerve ablation for the treatment of chronic low back pain: 12-month results

Abstract: IntroductionVertebral endplates, innervated by the basivertebral nerve (BVN), are a source of chronic low back pain correlated with Modic changes. A randomized trial comparing BVN ablation to standard care (SC) recently reported results of an interim analysis. Here, we report the results of the full randomized trial, including the 3-month and 6-month between-arm comparisons, 12-month treatment arm results, and 6-month outcomes of BVN ablation in the former SC arm.MethodsProspective, open label, 1:1 randomized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
49
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(51 citation statements)
references
References 33 publications
0
49
0
1
Order By: Relevance
“…The risk of this minimally invasive procedure remains low, with only one serious device-procedure related event reported in the literature for the 493 clinical study cases (including sham and crossover procedures) for an overall serious deviceprocedure related event rate of 0.2%. [12,14,15,21] The primary non-serious device-procedure related event reported in this study were transient leg and back pain events. Leg pain events were mild in nature, primarily treated with oral medications, and had a median resolution of 48.5 days.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…The risk of this minimally invasive procedure remains low, with only one serious device-procedure related event reported in the literature for the 493 clinical study cases (including sham and crossover procedures) for an overall serious deviceprocedure related event rate of 0.2%. [12,14,15,21] The primary non-serious device-procedure related event reported in this study were transient leg and back pain events. Leg pain events were mild in nature, primarily treated with oral medications, and had a median resolution of 48.5 days.…”
Section: Discussionmentioning
confidence: 85%
“…Likewise, in the 91% of SC arm patients that opted to cross to BVNA, similar results were observed, with reductions of 25.9 points in mean ODI and 3.8 cm in mean VAS from re-baseline at 6 months post ablation. Treatment outcomes for the BVNA remained durable through 12 months [15] . We report 24-month outcomes of the treatment arm for this second RCT and explore the applicability of these results in practice today.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…Numerous clinical studies, reviews, meta-analyses, and society guidelines have reported the safety and clinical efficacy of BVNA in the treatment of vertebral pain [42][43][44][45][46][47][48][49][50][51][52][53]115,116,[132][133][134][135][136]. Becker et al's study in 2017 reported that BVNA improved function at 6 weeks, 3, 6, and 12 months, with at least a 10-point reduction in ODI in 81% of subjects, as well as clinically meaningful improvement in pain scores and QoL [53].…”
Section: Basivertebral Nerve Ablationmentioning
confidence: 99%
“…The subsequent data showed only 4% of subjects received spinal injections after BVNA, suggesting that this intervention effectively reduces symptoms and minimizes additional health care costs. Smuck et al reported BVNA superiority to the standard of care (medications, therapy, and spinal injections) at 3-, 6-, and 12-month intervals for improved pain, function and QoL [42]. However, opioid use did not differ between groups.…”
Section: Basivertebral Nerve Ablationmentioning
confidence: 99%